The role of the theatrical technical supervisor in developing the skills of preparatory stage learners (Al-Academy, 2023)
The current study aimed to identify the role of the theatrical technical supervisor in developing and enhancing the skills of middle school students in Baghdad. The sample consisted of 73% of the original community of theatrical technical supervisors, randomly selected from those working in the first, second, and third educational directorates in the Rassafa and Karkh areas. The sample size was 32 theatrical technical supervisors. The study used a questionnaire to collect data on three axes: the cognitive skills developed by the theatrical technical supervisor, the voice and speech skills developed by the supervisor, and the body movement skills developed by the supervisor. The results showed that the theatrical technical supervisor plays a significant role in developing and enhancing the skills of middle school students in Baghdad, with body movement skills being the most developed, followed by cognitive skills, then voice and speech skills. The study recommends organizing training courses and programs for teachers to use the school theater as an educational tool, preparing a guide for school theater activities, and conducting further studies from the perspective of students to shed more light on the role of school theater in the educational process.